Occupational injuries among Royal Malaysian Navy personnel, Lumut base, Perak - Zainal Othman; KG Rampal (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Cases of occupational injuries are rising in Malaysia due to increasing numbers of workers in this country .A case-control study was conducted among the Royal Malaysian Navy personnel in Lumut base, Perak. The aim of this study is to evaluate factors contributing to occupational injuries among navy personnel who attended to Hospital Angkatan Tentera TLDM in Lumut. Hundred and six cases respondance were selected as cases. It was then matched with another 106 respondance based on gender and type of work as control group. Chi-squared and paired t-test were used to test the univariate relationship between occupational injuries and factors under studied. Crude odds ratio were calculated for categorical factors. Significant association was found between ethnic groups where Malays have lower risk with odds ratio of 0.11. Trainees and ship crews were the main occupation category, which contribute to most injuries. There was a significant different (p<0.05) between perception towards safety measures and occurrence of injuries. There was also a significant relationship between respondance residents and place where injury occur. It was noted that those who stayed in the base were at increased risk to injury .Environmental related factors and equipment have no influence on occupational injuries during this study. In conclusion, better and more systematic preventive strategies and safety measures are needed in order to reduce accident, injuries and minimise its severity .